Effects of internet shutdown among medical students of a tertiary care hospital in Imphal, Manipur: a cross-sectional study - Laishram, Jalina; Singh, Khangembam Sonarjit; Huyam, Yaipharembi; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2023)
Background: The internet shutdown has become a global issue affecting the academic activities of medical students. Due to civil unrest in Manipur, a Northeastern state in India, the internet has been shut down for the past several months. Therefore, the study was undertaken with the objective to determine the magnitude of the effects of the internet shutdown among the medical students of a tertiary care hospital in Manipur. Methods: A cross-sectional study was conducted in July 2023 among 135 medical students of a tertiary care hospital using a convenience sampling method. Data were collected by using a self-administered structured questionnaire. Data analysis was done by using SPSS software version 26. Results: The mean age of the participants was 21±1.8 years. The study found that the majority (93.3%) of medical students opined that the internet shutdown affected their daily activities. Most of the participants (83.7%) stated that their study was affected by the current internet shutdown. Only (39.2%) of participants faced problems in submitting online forms. Most of the participants (71.1%) had a bad experience during the internet shutdown. Conclusions: The internet shutdown affected most of the participants in their daily activities. Most of the participants felt they were missing out on information and opportunities. Most of the participants rate their overall experiences as bad during the internet shutdown.